(untitled) (Asian-Australasian Journal of Food Safety and Security, 2019)
There were 17 districts under Dhaka, Chottogram, Sylhet, Rajshahi, Khulna and Mymensingh divisions selected for this study on the basis of Turkey farming. The total 52 number of farmers interviewed to conduct this study. Turkey rearing is a profitable agricultural practice to meet the protein requirement in developing countries like Bangladesh. This is not only a source of protein but also a rich source of minerals and vitamins. The semi-intensive rearing of turkey requires low capital investment and labor cost. The main objectives of the study were to know the present status of feeding and rearing system, problems and prospects and benefit cost ratio of turkey rearing in Bangladesh. The information that collected from the respondents were age, education, main occupation, family members, training, annual income, number of turkey in each batch, name of strain, mortality rate, vaccination and medication practice, current situation of antibiotic and growth promoter use, use of footbath, use of disinfectant for spraying in inside and outside of the farm, percentage of antibiotic and feed additives withdrawal period before marketing, source of vaccine and medicine at farmer level, consultants of the farmers for vaccine and medicine specially antibiotic use, vaccination and medication cost in a batch. The average cost for production of one kg meat is BDT 231.177 and average market price of one kg meat was about BDT 452.34. Asian Australas. J. Food Saf. Secur. 2019, 3(1), 48-52